(3GdHSjW aj GdJaSjQs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj, J (B468 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI GdCMRGH s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI GdThQi s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B25 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B245s
Keywords: (3GdJaSjQ hYdhe GdbQBfs